Learning English Language as a Second Language (ESL) by Iraqi University Students during the Outbreak of COVID-19: A Case- Study of Imam Kadhum College Students’ Challenges (Journal of the College of Basic Education, 2022)
When the World Health Organization announced COVID-19 as a global pandemic in 2020, the Iraqi government (like the rest of others) had to use preventive policies to control the spread of the virus. As a result of that, universities and schools have been closed to start then what is called ‘Distance Learning’, which paved the way for the continuity of the learning process. Distance or E. learning in higher education is a long-term concept. It is targeted at technology devices and www. The latter, actually, implies a problematic thing in Iraq due to the constant interruption. Poverty is another challenge added to the previous one that prevents far learning from becoming nearer and available in Iraqi homes. However, such a method of teaching originated in the earlier 18th century. Purpose: This research aimed to describe the experience of Iraqi academic staff members and university students with the E. Learning during the pandemic of covid-19. It is also targeted at answering the central question: what are the challenges encountered by Iraqi university students (Imam Kadhum college students) during their learning of the English language in Covid-19. Seeking distance education trends during the 2019- 2020 coronavirus pandemic is not another goal of the research at hand.